2019
DOI: 10.1111/jfpe.13134
|View full text |Cite
|
Sign up to set email alerts
|

Moisture sorption isotherm and shelf‐life prediction of anticaking agent incorporated spray‐dried soursop (Annona muricata L.) powder

Abstract: The moisture sorption isotherm (MSI) and shelf lives of soursop powders that had been incorporated with two commercial anticaking agents, calcium silicate (CS) and tricalcium phosphate (TCP), and inserted into aluminum laminated polyethylene pouches under room (RT, 25 ± 1 C) and elevated (ET, 38 ± 1 C) temperature, maintained at 93 ± 1% RH, were investigated. The powder possessed a Type III Brunauer's classification isotherm curve. The monolayer moisture content (M o ) was 0.023 ± 0.001 g H 2 O/g ds. A combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 40 publications
1
11
0
1
Order By: Relevance
“…The K value close to 1 indicates that water beside the monolayer exhibits properties of pure liquid water. 65 The K value remained within the range recorded in the literature for biodegradable films (0.92-0.98). 66…”
Section: Sorption Modeling Tablessupporting
confidence: 77%
“…The K value close to 1 indicates that water beside the monolayer exhibits properties of pure liquid water. 65 The K value remained within the range recorded in the literature for biodegradable films (0.92-0.98). 66…”
Section: Sorption Modeling Tablessupporting
confidence: 77%
“…Most evaluations of MSI models are based on their statistical goodness of fit over the experimental range of a w , but not on their applicability to shelf-life estimation. There are some studies that used the nonlinear MSIs for estimating shelf life: the Oswin equation (Hao et al, 2016); GAB equation (Abdissa et al, 2020;Chang et al, 2019;Koç et al, 2010;Ramachandra & Rao, 2013;Rangarao et al, 1995;Siripatrawan, 2009); and other nonlinear equations (Macedo et al, 2013;Mizrahi et al, 1970). Because all the nonlinear MSI equations mentioned above are somewhat difficult to use to estimate the moisture increase of packaged foods, a simple linear equation model covering only the lower a w range was incorporated into moisture transfer equations to develop an analytical solution for the calculation of shelf life by Labuza et al (1972) and then applied to many cases to estimate dried food shelf life (An et al, 2018;Escobedo-Avellaneda et al, 2012;Gichau et al, 2020;Yaptenco et al, 2017).…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Silicon dioxide (2% w/w) and calcium silicate (2% w/w) were able to improve the physical stability in terms of particle size of powdered sodium ascorbate (Vitamin C) (Lipasek et al, 2011). In the work of Chang et al (2019), it was reported that calcium phosphate was a more stable anticaking agent as compared to calcium silicate. Calcium phosphate has a higher glass transition temperature that causes better prevention of moisture adsorption as it forms a protection barrier on the dried powder.…”
Section: Effects Of Different Anticaking Agents On Properties Of 'Cemmentioning
confidence: 99%
“…The addition of calcium phosphate, calcium silicate or calcium oxide has been found to give a favorable free-flowing characteristic to powder when it is stored (Jaya & Das, 2005;Jaya et al, 2006). Chang et al (2019) incorporated calcium silicate and tricalcium phosphate in the production of soursop powder. The addition of 0.25% calcium phosphate in the production of Garcinia indica powder and pineapple powder produced powders (Nayak & Rastogi, 2010;Phanindrakumar et al, 2005).…”
Section: Introductionmentioning
confidence: 99%